The primacy of the subjective : foundations for a unified theory of mind and language - Georgalis, Nicholas, 1944- (Cambridge, Mass. : MIT Press, 2006)
"In this original monograph, Nicholas Georgalis proposes that the concept of minimal content is fundamental both to the philosophy of mind and to the philosophy of language. He argues that to understand mind and language requires minimal content - a narrow, first-person, non-phenomenal concept that represents the subject of an agent's intentional state as the agent conceives it. Orthodox third-person objective methodology must be supplemented with first-person subjective methodology. Georgalis demonstrates limitations of a strictly third-person methodology in the study of mind and language and argues that these deficiencies can be corrected only by the incorporation of a first-person methodology
The fundamental intentional state -- Minimal content and some failures of third-person methodologies -- Consciousness and subjectivity -- Physicalism, the explanatory gap, and chaos -- Representation and the first-person perspective -- Minimal content and the ambiguity of sensory terms -- Rethinking Burge's thought experiment -- Minimal content, Quine, and determinate meaning -- Ontology downgraded all the way
"A Bradford book."
Includes bibliographical references (p. [341]-349) and index
Keywords: Philosophy of mind; Subject (Philosophy); Intentionality (Philosophy); Language and languages -- Philosophy